Influence of Work Culture, Compensation on Staff Performance, with Organizational Commitment, Public Works. - Muhammad Irfani Hendri (Yayasan Multidimensi Kreatif, 2023)
This study analyzes the influence of work culture and compensation on employee performance with organizational commitment as an intervening variable. The research is conducted in the Office of Public Works and Spatial Planning in a typical city. The population consists of 79 employees, and the entire population is used as the sample (saturated sample). Data collection is done through a questionnaire. Path analysis and Smart PLS version 3.3.3 are employed for the research model.Results show that work culture significantly and positively affects employee performance. Work culture also has a positive and significant impact on organizational commitment. Organizational commitment is found to have a positive and significant effect on employee performance. However, compensation does not have a significant positive effect on employee performance or organizational commitment. Moreover, organizational culture has a positive but insignificant influence on employee performance through organizational commitment. Compensation also has a positive but not significant effect on employee performance through commitment..